Syntactic information in bilingual Lithuanian lexicography - Griškevičienė, Aurelija (Lietuvių kalba, 2013)
The main aim of the article is to analyse which types of syntactic information should be included in bilingual dictionaries where Lithuanian is the target language. The article discusses specific features of bidirectional dictionaries and differences between the syntactic information given in bilingual and monolingual dictionaries. Also discussed are principles for selecting syntactic information on Lithuanian as a target language, general syntactic features which are relevant in lexicography, ways of presenting government and valency and the importance of contrastive analysis for bilingual lexicography. Although syntactic information on lemmas and their equivalents is not a new subject in lexicographic theory and practice, syntactic information on Lithuanian as a target language has not yet been investigated, as no dictionaries for foreign users of Lithuanian have been compiled and published. The investigation is mostly based on experience and empirical data from the “Norwegian-Lithuanian dictionary”.The analysis leads to the conclusion that the most important information to provide about Lithuanian equivalents in bilingual dictionaries is verb government and valency. The most valuable information for the users of bilingual dictionaries illustrates the syntactic differences between the source and the target language, and this information can be identified by applying a contrastive method. The relevant syntactic information can be given next to the equivalents or in the examples. Case marking, obligatory use with prepositions as well as subordination of infinitive constructions can be shown next to the equivalents. As a minimum, the syntactic information on Lithuanian verbs should state if the verb takes another object case than the accusative. It is necessary to provide equivalents with the obligatory components of valency, while facultative components might be shown in the examples. Syntactic information should be provided for phrases as well as for single-word equivalents. In the examples one can show the variety of the syntactic features of the Lithuanian equivalents and highlight the differences between the syntactic features of the Norwegian lemmas and their Lithuanian equivalents. Examples can also be used to show specific syntactic constructions which do not exist in Lithuanian and provide information on congruous syntactic features of both languages.It is hardly possible to present the syntactic features of both languages equally detailed in bilingual bidirectional dictionaries. As lemma lists and examples are usually compiled on the basis of the source language, it usually turns out that the target language is provided with less information, and it is complicated to analyse and highlight the grammar of all the equivalents of the source language.
Keywords: none